2017
DOI: 10.1021/acsami.7b14415
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Photoresponse of InAs Nanowires

Abstract: We report on individual-InAs nanowire optoelectronic devices which can be tailored to exhibit either negative or positive photoconductivity (NPC or PPC). The NPC photoresponse time and magnitude is found to be highly tunable by varying the nanowire diameter under controlled growth conditions. Using hysteresis characterization, we decouple the observed photoexcitation-induced hot electron trapping from conventional electric field-induced trapping to gain a fundamental insight into the interface trap states resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 53 publications
2
71
0
5
Order By: Relevance
“…Alternatively, applying an insulating layer and a contacting layer on top of the nanowire, a top-gated FET can be achieved as shown in Figure 2d [11,35]. Such transistor structures have been used for InAs photodetectors to manipulate electron trapping sites formed by the native oxide, leading to tunable positive or negative photoconductivity [11,36,37,80,81]. Although most semiconductors have increased conductivity under photoexcitation (positive photoconductivity (PPC)), Alexander-Webber et al reported an unusual negative photoconductivity (NPC) of InAs nanowire-based phototransistors under visible light illumination as shown in Figure 2b [36].…”
Section: Phototransistorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, applying an insulating layer and a contacting layer on top of the nanowire, a top-gated FET can be achieved as shown in Figure 2d [11,35]. Such transistor structures have been used for InAs photodetectors to manipulate electron trapping sites formed by the native oxide, leading to tunable positive or negative photoconductivity [11,36,37,80,81]. Although most semiconductors have increased conductivity under photoexcitation (positive photoconductivity (PPC)), Alexander-Webber et al reported an unusual negative photoconductivity (NPC) of InAs nanowire-based phototransistors under visible light illumination as shown in Figure 2b [36].…”
Section: Phototransistorsmentioning
confidence: 99%
“…Such transistor structures have been used for InAs photodetectors to manipulate electron trapping sites formed by the native oxide, leading to tunable positive or negative photoconductivity [11,36,37,80,81]. Although most semiconductors have increased conductivity under photoexcitation (positive photoconductivity (PPC)), Alexander-Webber et al reported an unusual negative photoconductivity (NPC) of InAs nanowire-based phototransistors under visible light illumination as shown in Figure 2b [36]. This surface photo-gating effect may be explained by the fact [36,80] that the free carriers in the InAs nanowire could be excited into charge trapping sites located in the surface native oxide after the absorption of light with photon energy much higher than the bandgap.…”
Section: Phototransistorsmentioning
confidence: 99%
See 2 more Smart Citations
“…III-V semiconductors exhibit exceptional (opto)electronic properties, which makes them ideal functional materials in photovoltaics, [1][2][3][4] photoelectrochemistry, [5][6][7] light sensors, [8][9][10] light sources 11 and high speed devices. 12,13 The growth mechanisms of III-V semiconductors in the vapour phase have been extensively studied, [14][15][16] shedding light on the effect of growth parameters on the strain, crystallinity and impurities.…”
Section: Introductionmentioning
confidence: 99%